Knowledge and Skill of Anganwadi Workers in Growth Monitoring in an Urban Slum of Central Part of Karnataka - Undi, Malatesh; Annadani, Rachana Rajashekhara; Rajashekara, Sindhu (Indian Journal of Community Health, 2019)
Background: In India, Anganwadi Workers (AWWs) maintain the growth record of all the under-five years’ children in their area under ICDS. This task requires technical skill of proper weighing, plotting weight on growth charts, interpreting growth curve and using the growth card as a tool for educating mothers. In urban slums, their knowledge and skills are rarely assessed. Objectives: To assess the knowledge and skill of AWWs regarding growth monitoring of under-five years’ children. Methods: This cross-sectional study was done in an urban slum in central part of Karnataka. After obtaining ethical clearance, data was collected from 20 AWWs and 100 under-five children using a structured questionnaire (modified and adapted from ICDS manual). Data was analyzed using MS-Excel 2010.Results: All AWWs correctly interpreted growth chart but 60.0% didn’t know the expected weight for age or number of times a child should be weighed. 70% had inadequate skills to determine correct age of child and 30% erred while measuring the weight of child. Conclusions: Majority of AWW had adequate knowledge regarding growth monitoring but lacked skills in crucial steps like age determination and weighing the child. Training programme must ensure that the AWW learn and practices these skills.